2007
DOI: 10.1111/j.1460-9568.2007.05863.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane Ca2+‐ATPase in the cilia of olfactory receptor neurons: possible role in Ca2+ clearance

Abstract: Olfactory sensory neurons respond to odorants increasing Ca(2+) concentrations in their chemosensory cilia. Calcium enters the cilia through cAMP-gated channels, activating Ca(2+)-dependent chloride or potassium channels. Calcium also has a fundamental role in odour adaptation, regulating cAMP turnover rate and the affinity of the cyclic nucleotide-gated channels for cAMP. It has been shown that a Na(+)/Ca(2+) exchanger (NCX) extrudes Ca(2+) from the cilia. Here we confirm previous evidence that olfactory cili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 47 publications
5
55
0
Order By: Relevance
“…Using electrophysiological criteria it has been reported that NCX is the major means of Ca 2+ extrusion following odor-evoked stimulation of the apical region of amphibian and mouse OSNs [50], [51]. The demonstration of NCX1 in isolated cilia by immunoblotting [52] is consistent with these reports. This has not been previously analyzed using Ca 2+ imaging of mouse OSN knobs.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Using electrophysiological criteria it has been reported that NCX is the major means of Ca 2+ extrusion following odor-evoked stimulation of the apical region of amphibian and mouse OSNs [50], [51]. The demonstration of NCX1 in isolated cilia by immunoblotting [52] is consistent with these reports. This has not been previously analyzed using Ca 2+ imaging of mouse OSN knobs.…”
Section: Resultssupporting
confidence: 77%
“…This has not been previously analyzed using Ca 2+ imaging of mouse OSN knobs. Recent reports suggests that PMCA may also play a significant role in Ca 2+ removal in the rat [52] and mouse [53] OSNs. Therefore, we evaluated the contribution of each Ca 2+ clearance mechanism to the removal of elevated Ca 2+ i .…”
Section: Resultsmentioning
confidence: 99%
“…The latter activate Ca 2 + -dependent Cl À channels (Cl Ca ) involved in excitatory odour transduction and/or Ca 2 + -dependent K + channels (K Ca ), which act in an inhibitory manner [1,2]. Ca 2 + levels are restored by a Na + /Ca 2 + exchanger and a plasma membrane Ca 2 + -ATPase [3]. Moreover, Ca 2 + binding to calmodulin mediates adaptation to odour signals by interaction with various targets [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Ca 2+ /Calmodulin (Ca 2+ /CaM) can bind to CNG channels, promoting a decrease in its affinity to cAMP [15], a process that seems to be involved in STA. Since cAMP opens CNG channels leading to Ca 2+ influx that induces STA [11], Ca 2+ extrusion mainly through Na + /Ca 2+ and K + exchangers (NCKX) [16][18] and, possibly, plasma membrane Ca 2+ -ATPases (PMCA) [19][22] leads to the resetting the cellular resting state. There are evidences that K + -independent Na + /Ca 2+ exchangers (NCX) and NCKX are present in mammalian OSNs [23], [24].…”
Section: Introductionmentioning
confidence: 99%